Indian sociological thought - Nagla, B. K. (Jaipur: Rawat Publications, 2008)
On the writings of prominent Indian sociologists.
Includes bibliographical references and index.
Keywords: SOCIOLOGISTS- INDIA; SOCIOLOGY- INDIA